DIGITAL ENGAGEMENT IN CHILD ISLAMIC BOARDING SCHOOLS: CORRELATION BETWEEN APPLICATION USAGE AND GUARDIANS' SATISFACTION - Taufikin Taufikin; Ahmad Hariyadi; Muhammad Ihsan Dacholfany; Dwinarko Dwinarko; Tri Cicik Wijayanti; Gulnaz Fatma (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aimed the association between intensity of PPATQ-RF ku application usage and guardians’ satisfaction, providing an evidence base for more effective technology-enabled services. A quantitative design was employed using a structured questionnaire administered to 60 guardians from diverse regions and age groups. Data were analyzed using descriptive statistics, item validity tests, reliability analysis, Pearson’s correlation, and simple linear regression. The instrument demonstrated high internal consistency (Cronbach’s alpha = 0.838) and all items met validity criteria. A moderate, statistically significant positive correlation emerged between application usage and satisfaction (r = 0.573; p < 0.05). The regression model Y=11.948+0.699XY = 11.948 + 0.699X accounted for 32.9% of the variance in satisfaction. These findings indicated that optimizing application use can enhance guardians’ satisfaction, while recognizing that other determinants outside the application continue to exert substantial influence. These findings suggested that optimizing the app's use can increase the satisfaction of students’ guardians, while acknowledging that other factors beyond the app still have a significant influence. This study offers concrete managerial implications by identifying priority areas for improvement, particularly regarding system accessibility, information completeness, and feature optimization, thereby enabling boarding school administrators to design digital service strategies that are more responsive, integrated, and user-oriented.